2020
DOI: 10.1063/5.0029307
|View full text |Cite
|
Sign up to set email alerts
|

Covalent incorporation of diphenylanthracene in oxotriphenylhexanoate organogels as a quasi-solid photon upconversion matrix

Abstract: Note: This paper is part of the JCP Special Topic on Up-and Down-Conversion in Molecules and Materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…While these results are interesting on their own, one must consider in what settings intra-UC is anticipated to be of importance. As solid-state solutions are a desirable path moving forward, it is in the context of restricted molecular diffusion these results must be interpreted. , With respect to this, it is improbable that the TETA mechanism will be active in future solid-state systems where interactions between multichromophoric annihilators are hampered. These implications are strengthened by the results from the study by Dzebo et al, where large DPA annihilator frameworks showed better UC performance than DPA when put inside a rigid polymer matrix .…”
Section: Resultsmentioning
confidence: 99%
“…While these results are interesting on their own, one must consider in what settings intra-UC is anticipated to be of importance. As solid-state solutions are a desirable path moving forward, it is in the context of restricted molecular diffusion these results must be interpreted. , With respect to this, it is improbable that the TETA mechanism will be active in future solid-state systems where interactions between multichromophoric annihilators are hampered. These implications are strengthened by the results from the study by Dzebo et al, where large DPA annihilator frameworks showed better UC performance than DPA when put inside a rigid polymer matrix .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, TTET and TTA processes can be inhibited by the presence of O 2 that quenches the triplet excited states. 10 An important step forward in the application of TTA-UC systems in real devices under air-equilibrated conditions is the incorporation of the antenna and the emitter pair into protecting environments, [12][13][14][15] preserving the inter-chromophoric distances necessary to make efficient bimolecular processes. Therefore, the encapsulation of the organic chromophores presents multiple advantages.…”
Section: Introductionmentioning
confidence: 99%
“…S17-S19, ESI †). The only literature systems we examined for which our model could not fit the TTA-UC data were gels 41,42 (Fig. S20, ESI †), and TTA-UC devices.…”
Section: The Challenge Of Determining I Th Experimentallymentioning
confidence: 99%